(untitled) (Journal of the College of Basic Education, 2022)
Love... This rebellious signifier is not bounded by borders and does not contain a definition. It has baffled scholars and preoccupied the minds of jurists and theorists, old and new. They said about it and wrote books and articles about it, but it refused to submit to all these sayings and these theories. He mocked the definitions of Plato and Aristotle and the approaches of Al-Jahiz and Ibn Hazm Al-Andalusi. Those who tried to define it and explain its types and ranks, so they make for it a beginning or a peak and a foothill, and they make man’s love for his Creator the highest kind of love, as it means for Muslim philosophers obedience to the Almighty Creator, adherence to His orders and avoiding His prohibitions, a desire for heaven and fear of hell.